(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Improving Students’ Ability to Use Biological Learning Sets Approach Class XI IPA 1 SMA Negeri 9 Pekanbaru. Based on observations made by researchers, it appears that the activeness and performance of students is not optimal, 65% of students do not respond to the material and questions from the teacher. With the SETS (Science, Environment, Technology, and Society) approach in learning biology it is hoped that students can master and apply it. From the results of observations in the first and second cycles obtained 55.6% of students completeness, while in the second cycle 100% completeness of students. Here an increase of 44.4% student completeness. The use of animation-based demonstration methods can be used in a concerted manner to obtain maximum results. Keywords: student ability, SETS, Biology Abstrak: Meningkatkan Kemampuan Siswa Menggunakan Pendekatan Sets Pembelajaran Biologi Kelas XI IPA 1 SMA Negeri 9 Pekanbaru. Berdasarkan observasi yang dilakukan peneliti, tampak bahwa keaktifan dan kinerja peserta didik belum optimal, 65% peserta didik kurang memberi respon terhadap materi dan pertanyaan dari guru. Dengan pendekatan SETS (Science, Environment, Technology, and Society) dalam pembelajaran biologi diharapankan peserta didik dapat menguasai dan menerapkannya. Dari hasil observasi pada siklus I dan II diperoleh hasil 55,6 % ketuntasan siswa, sedangkan pada siklus II 100 % ketuntasan siswa. Disini terjadi peningkatan sebesar 44.4 % ketuntasan siswa. Penggunaan metode demontrasi berbasis animasi bisa digunakan secara berkesimabungan untuk memperoleh hasil yang maksimal. Kata Kunci: kemampuan siswa, SETS, Biologi